On Paths of Imagination. Pico’s Way towards Understanding Man - Wawrzonkowski, Krzysztof (Ruch Filozoficzny, 2016)
The aim of the following article is to reconstruct the sources of Gianfrancesco Pico della Mirandola’s (1469-1533) concept of imagination. Aristotle’s views presented in De Anima are their core. However, in order to present the full picture of the concept, I also refer to Poetics. At the same time I try to show some connection between the philosophical problems undertaken by Pico and his private life. My claim is that it was his need of understanding the surrounding world, including the actions of his closest family, which made him search for a philosophical tool that would help him in that respect. He found what he was looking for in the Stagirite’s views, which he attempted to supplement with the treads of Christian thought. Armed in such a way he wanted to change his own life as well as that of his family.